2018
DOI: 10.24926/jcotr.v25i2.2121
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing Reflection and Integrative Learning in First-Year Seminar Courses

Abstract: First-Year Seminar (FYS) or First-Year Experience (FYE) courses help college students transition to college, learn valuable academic skills, and create successful habits. This research analyzes the benefit of reorganizing FYS curriculum around reflection and integrative learning, by comparing students who participated in this redesigned curriculum with those who participated in a skills-based, extended orientation first-year seminar course. The two groups were compared on several measures, including perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
0
8
0
2
Order By: Relevance
“…In this study, we situate reflection as both evidence for and part of the larger integrative learning process. Indeed, as previously noted, the two go hand-in-hand, with one component playing an integral role in the other (Aguila 2016; Rust and Korstange 2018). For the purposes of this study, too, we have treated reflection as primarily a linguistic construct, and our analysis of it as an act of interpreting the latent structures that underlay that construct.…”
Section: Discussionmentioning
confidence: 85%
“…In this study, we situate reflection as both evidence for and part of the larger integrative learning process. Indeed, as previously noted, the two go hand-in-hand, with one component playing an integral role in the other (Aguila 2016; Rust and Korstange 2018). For the purposes of this study, too, we have treated reflection as primarily a linguistic construct, and our analysis of it as an act of interpreting the latent structures that underlay that construct.…”
Section: Discussionmentioning
confidence: 85%
“…A year later, we returned to NCTE in Houston, Texas. We read excerpts of this manuscript alongside two teams of faculty authors sharing findings of YPAR inquiries at their universities, further reflecting and learning on a panel presentation on experiences across our first year (Rust & Korstange, 2018).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Undergraduate participants discussed possibilities for student affairs educators to engage "proactive outreach" toward "creating community and demonstrating care for individual student circumstances" (p. 1). Rust and Korstange (2018) found benefits for students participating in first-year seminar courses through "prioritizing reflection and integrative learning" (p. 76). Morgan et al (2020), in a study examining the "orientation and transitional experiences" of Black undergraduate students attending a public research university in an urban setting, found that participants observed a "shortage of Black faculty, limited Black cultural programming, and a need for identity-based space" (p. 1).…”
Section: Undergraduate Preservice Teachers Of Color and The Urgency Omentioning
confidence: 99%
See 2 more Smart Citations